2010
DOI: 10.1111/j.1365-2672.2010.04779.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Acanthamoeba species related to amoebic encephalitis and nonpathogenic free-living amoeba species from the rice field

Abstract: The integration of field survey, clinical data and morphological and genetic examination represents a sound strategy for investigation of the possible role of free-living amoebae in causing human diseases. Future work should include investigating the potential contributory role of other nonpathogenic free-living protozoa in disease of livestock or even human.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…This heterologous recognition may be caused by the relative proximity of these species in evolutionary terms. Such proximity is shown by phylogenetic analysis …”
Section: Discussionmentioning
confidence: 86%
“…This heterologous recognition may be caused by the relative proximity of these species in evolutionary terms. Such proximity is shown by phylogenetic analysis …”
Section: Discussionmentioning
confidence: 86%
“…The present study is the first comprehensive investigation on surface and tap water and also indoor swimming pools of Shiraz City which has been conducted to identify the pathogenic free-living amoeba by molecular method. Infections owing to Acanthamoeba have been increased worldwide recently, which is more likely related to the presence of Acanthamoeba in the natural environment, especially in water sources (Liang et al, 2010). Previous study looking at various samples revealed that medical instrumentation, air conditioners, windows, floors, sinks, water taps, bathrooms, and showers could be a possible source of Acanthamoeba in Iran (Lasjerdi et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The protistan genus Acanthamoeba comprises several species of the opportunistic and pathogenic free-living amoebae, widespread in many types of environments and playing a role of major microbial predators (Corsaro and Venditti 2010;Liang et al 2010). The protistan genus Acanthamoeba species have been classified into three distinct morphological groups based largely on the cyst morphology of the species and encompassing more than 25 nominal species (Booton et al 2005;Visvesvara and Schuster 2008a, b).…”
Section: Introductionmentioning
confidence: 98%